Allometric framework for estimating soil C sequestration on smallholder farmer fields - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The framework has been developed on a limited number of farmer fields and should be validated before it can be disseminated to other agro-ecosystems.